A rapid and novel method for the synthesis of 5-substituted 1H-tetrazole catalyzed by exceptional reusable monodisperse Pt NPs@AC under the microwave irradiation1. Issue 84 (16th September 2015) - Erken, Esma; Esirden, İbrahim; Kaya, Muharrem; Sen, Fatih
<x xml:space="preserve">Abstract</x> Monodisperse Pt NPs@AC catalyst showed excellent yield, one of the shortest reaction time for the synthesis of 5-substituted 1H-tetrazoles under the microwave irradiation.